Особливості проектування логістичних систем вантажних перевезень - Гурч, Л. М.; Школьна, О. В. (Видавництво Львівської політехніки, 2012)
Розгнуто і проаналізовано теоретичні аспекти організації і проектування логістичних систем організації перевезень вантажів, розроблено рекомендації щодо впровадження логістичної системи. Analysis of theoretical aspects of organization and design of logistical system of cargo transportation, development of logistics system implementation recommendations, are discussed in this article. Analysis of theoretical aspects of organization and design of logistical system of cargo transportation, development of logistics system implementation recommendations, are discussed in this article.
The peculiarities of loads transportation logistics systems design
Keywords: логістичні системи; проектування логістичних систем; ефективність надання транспортних послуг; транспортна логістика; вантажні перевезення; logistical system; design of logistical system